Enhancing healthcare accessibility through telehealth for justice impacted individuals - Williams, Karmen S.; Singh, Marianna J.; Elumn, Johanna E.; Threats, Megan; Sha, Yongjie; McCall, Terika; Wang, Karen; Massey, Bria; Peng, Mary L.; Wiley, Kevin (Frontiers in Public Health, 2024)
Telehealth is a great tool that makes accessing healthcare easier for those incarcerated and can help with reentry into the general society. Justice impacted individuals face many hardships including adverse health outcomes which can be mitigated through access to telehealth services and providers. During the federally recognized Covid-19 pandemic the need for accessible healthcare was exacerbated and telehealth use surged. While access to telehealth should be considered a necessity, there are many challenges and barriers for justice impacted individuals to be able to utilize this service. This perspective examines aspects of accessibility, pandemic, policy, digital tools, and ethical and social considerations of telehealth in correctional facilities. Carceral facilities should continue to innovate and invest in telehealth to revolutionize healthcare delivery, improve health outcomes, and promote positive rehabilitation for justice impacted individuals.